Elections in Britain Today - Leonard, Dick. author. aut Link
X, 237 p.
Keywords: An account of the ways in which the British electoral system works, this book answers central questions such as when are elections held and what happens on polling day? Also examined are issues such as why constituency boundaries are altered, how parties are organized and the role of the media.